EXPRESSION OF DIALECT WORDS IN THE NOVEL "THE LAND OF JUDAISM" - Tursunova Sanobar Najmiddinovna (Journals Park Publishing, 2023)
This article analyzes dialectal words, morphological, lexical, and phonetic features specific to the Tashkent dialect in Murad Mansur's novel " The land of judaism ". In addition, the effective use of the Tashkent dialect and children's speech words in the literary work is described.